Pembelajaran Tematik Berbasis Konstruktivisme dalam Meningkatkan Kreativitas Siswa SD/MI - Desy Yana Eka Saputri; Dhea Amanda Mutri; Miftahul Jannah; Najwa Putri Handayani; Agus Dwi Prasojo (LP2M STAI Darul Kamal NW Kembang Kerang, 2026)
Thematic learning is an approach that integrates various fields of study under a single theme, thereby creating more meaningful learning activities for students. However, the implementation of learning in elementary schools still tends to be teacher-centered, so student engagement in the learning process has not yet been optimal. Therefore, the application of teaching methods that encourage active student engagement is crucial through constructivist strategies, which promote enhanced understanding through direct experience and social interaction. This study aims to analyze the application of constructivist-based thematic learning in enhancing students’ creativity in elementary schools (SD/MI) and to examine the integration of these two approaches. The novelty of this research lies in the analysis of integration of thematic learning and the constructivist approach in enhancing creativity and critical thinking skills among elementary school students through a literature review. The research method used in this study is a literature review analyzed using a descriptive qualitative approach through a study of a number of relevant scientific articles. The results of this study found that constructivism-based thematic learning can strengthen students’ creativity, critical thinking, problem-solving skills, and confidence in expressing ideas. Thus, this approach has proven effective in the implementation of learning in elementary schools.